Downhill esophageal varices associated with superior vena cava syndrome – A case report (Research, Society and Development, 2022)
Objective: Esophageal varices are an important cause of digestive bleeding, with uphill varices secondary to portal hypertension being the most common cause. Downhill esophageal varices are rare, are related to superior vena cava obstruction, and require investigation as to their etiology, as appropriate treatment is related to the underlying cause and is essential to reduce the risk of complications. Methodology: A review of the patient's chart was carried out, as well as an extensive literature search on downhill esophageal varices, with a detailed study of their etiology, pathophysiology, diagnosis, and treatment. The correlations between the case and the findings in the literature are also presented. Case report: A 52-year-old patient presented with clinical manifestations of superior vena cava syndrome and endoscopic findings of downhill esophageal varices. A complementary investigation with computed tomography of the chest was performed, and chronic thrombosis of the superior vena cava with extensive collateral circulation was diagnosed. The investigation of thrombophilia was negative, and the etiology of the thrombosis was defined as idiopathic. Conclusion: The importance of recognizing, diagnosing downhill esophageal varices, and understanding their pathophysiology for adequate etiological investigation and early treatment, as well as reducing the risks of gastrointestinal bleeding, are highlighted in this case.